Peri basileias - Murray, O; Murray, Oswyn (1971)
The thesis seeks to investigate primarily the philosophical treatises with the title pe?? [?] which were written in the Hellenistic period, that is from the age of Alexander to the end of the Roman Republic. It aims to discover their contents, purposes, similarities and differences, and so to illuminate the attitudes of philosophers and other educated men to the Hellenistic monarchies. Each work discussed is put as far as possible in its historical context in order to demonstrate the relationship between philosophical theory and political practice, and in order to show how philosophers influenced and were influenced by the kings they advised. The Introduction discusses the origins and growth of ideas about kingship in the archaic and classical periods: it treats in outline the main influences on later thought. Part I deals with the known evidence for works pe?? [?]. Chapter 1 concerns treatises addressed to Alexander or written during his lifetime. In particular the evidence for Aristotle's relationship with Alexander is discussed in connection with his alleged pe?? [?]; his section on kingship in book iii of the Politics is analysed; and the Arabic treatise recently discovered is shown to be a forgery of Roman imperial date. The works of Xenocrates and Anaxarchus are also discussed. This chapter is particularly concerned with the rivalries between the various philosophers around the figure of Alexander. Chapter 2 deals with the other Hellenistic treatises whose authorship is known, by philosophical schools - the Peripatetics, Epicureans, Stoics, and 'Pythagoreans'. Chapter 3 gives the fragmentary evidence from papyri and Suidas. Part II attempts to fill out this picture, and show the inter-relationship between native and Greek traditions in the world of Hellenistic literature, by taking three extant prose works where a theoretical attitude to kingship can be seen. Again these works are discussed in detail, reconstructed where necessary, and an attempt is made to date them and relate them to their historical background. Chapter 1 deals with the work of Hecataeus of Abdera on Egypt, and especially the section on Pharaonic kingship (preserved in Diodorus book i). Chapter 2 discusses the letter of Aristeas to Philocrates, and especially the relationship between the section on kingship which it contains and the purpose of the work as a whole. Chapter 3 is an analysis of Philodemus, On the Good King according to Homer, which attempts to show the purpose of the work, and the limitations on the use of ideas of kingship in the Roman political world of the late Republic. There are four appendices, the last of which contains a translation of the new text of the Arabic letter of Aristotle to Alexander On Government, by myself and S.M. Stern; it is given here purely for the convenience of the examiners, since it is unpublished, and should not be considered part of the thesis proper.